Optimization of Pre-Treatment Methods in Reactive Dye Printing on Handloom Kenaf Fabrics - Haris, Muhammad Naoval; Maghfiroh, Maghfiroh; Basyaib, Fainuzha Farhan; Ramadhani, Farchan Mushaf Al (P3M Politeknik Negeri Media Kreatif, 2025)
The use of kenaf fiber as an eco-friendly textile material faces challenges in the dye printing process, particularly due to its limited dye absorption. This study aims to investigate and optimize various pre-treatment methods on handloom kenaf fabrics for reactive dye printing. A laboratory-based factorial design was employed, testing four pre-treatment variations: untreated, scouring, bleaching, and a combination of scouring and bleaching. Evaluations focused on color fastness to washing, rubbing, and perspiration, following national and international testing standards. Results indicated that single bleaching treatment yielded the most optimal print outcomes, characterized by bright, uniform colors and superior fastness properties, especially under dry rubbing and washing. The combined scouring-bleaching method produced inconsistent results, likely due to fiber degradation caused by over-treatment. It is concluded that single-step bleaching is the most effective pre-treatment for reactive dye printing on handloom kenaf fabrics. This research contributes to the advancement of sustainable textile processing based on natural fibers.